Clinical Outcomes and Prognostic Analysis of 101 Patients of Central Neurocytoma: A 10-Year Treatment Experience at a Single Institution - Xie, Qiongxuan; Xie, Bin; Ou, Ludi; Wang, Min; Tang, Ziqing; He, Yuxiang; Yang, Xiaoyu; Hong, Jidong; Lyu, Zhiping; Wei, Rui (Frontiers in Oncology, 2022)
ABSTRACT Objective: Central neurocytoma (CN) is a rare type of tumor that currently lacks an optimal treatment protocol. This study aimed to explore the clinical outcomes of CN in a cohort of 101 patients and identify prognostic factors associated with multiple treatment modalities. Methods: This monocentric study retrospectively analyzed the clinical data of 101 CN patients who underwent surgical resection. The patients were followed up, and their overall survival (OS) and progression-free survival (PFS) were calculated. Results: For the entire cohort, the 5- and 10-year OS rates were 88.7% and 82.8%, respectively, and the 5- and 10-year PFS rates were 86.5% and 64.9%, respectively. Of the 82 (81.19%) patients with CN who underwent gross total resection (GTR), 28 (28/82, 34.1%) also received radiotherapy (RT). Of the 19 (18.81%) patients with CN who underwent subtotal resection (STR), 11 (11/19, 57.9%) also received RT or stereotactic radiosurgery (SRS). Compared to STR, GTR significantly improved the 5-year OS (92.4% vs. 72.4%, P=0.011) and PFS (92.4% vs. 60.4%, P=0.009) rates. Radiotherapy did not affect OS in the GTR group (p=0.602), but it had a statistically significant effect on OS in the STR group (p < 0.001). However, the OS (P=0.842) and PFS (P=0.915) in the STR plus radiotherapy group were comparable to those in the GTR alone group. Compared to STR alone, STR plus radiotherapy improved the 5-year PFS rate from 25% to 75% in patients with atypical CN (P=0.004). Cox regression models and a competing risk model showed that the removal degree and radiotherapy were independent prognostic factors for survival. With improvements in modern radiotherapy techniques, severe radiotherapy toxicity was not observed. Conclusion: Our findings support the use of GTR whenever possible. Radiotherapy can improve the prognosis of patients who undergo STR, especially in atypical CNs having a higher tendency to relapse. Close imaging follow-up is necessary. Our findings will help clinicians to select optimal, individualized treatment strategies to improve OS and PFS for patients with CN.